2011
DOI: 10.1002/pbc.23054
|View full text |Cite
|
Sign up to set email alerts
|

Communication and language challenges experienced by Chinese and South Asian immigrant parents of children with cancer in Canada: Implications for health services delivery

Abstract: Language ability played an essential role in parents' healthcare experiences for pragmatic and social purposes. Language challenges can heighten systemic and socio-cultural barriers to accessing health information and resources. The provision of enhanced culturally and linguistically sensitive services may support immigrant families in their caregiving role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 28 publications
(44 reference statements)
2
72
0
1
Order By: Relevance
“…Conversely, studies of South Asian immigrant populations revealed no clear trends. One study [20] cited cultural differences as the most important barrier to accessing health care services among South Asian immigrants, while other studies listed lack of health literacy/ limited awareness of disorder [27,28], and language barriers [30,31] as most significant.…”
Section: Studies Of Specific Cultural and Linguistic Groupsmentioning
confidence: 97%
See 2 more Smart Citations
“…Conversely, studies of South Asian immigrant populations revealed no clear trends. One study [20] cited cultural differences as the most important barrier to accessing health care services among South Asian immigrants, while other studies listed lack of health literacy/ limited awareness of disorder [27,28], and language barriers [30,31] as most significant.…”
Section: Studies Of Specific Cultural and Linguistic Groupsmentioning
confidence: 97%
“…Other specific groups studied were Iranian [22], Vietnamese [23], Portuguese-speaking [24], Francophone [25], and Asian [26]. Among studies of Chinese and South Asian immigrant populations, four research topics emerged: South Asian women's access to cervical cancer screening and mammography [27,28], health care access barriers for Chinese and South Asian seniors [19,20,29], health care access experiences of Chinese and South Asian parents of children with cancer [30,31], and barriers to accessing family physicians experienced by Chinese immigrants [17].…”
Section: Studies Of Specific Cultural and Linguistic Groupsmentioning
confidence: 98%
See 1 more Smart Citation
“…[54] This was an important contextual issue, but often the doctors did not recognize it, as they were used to directing their communication at the individual patient rather than at the family (specific skill). [38,51,157] For patients, their illnesses were connected to their community context and family; relations, culture and values were inseparable. [39,57,64,89,156,[158][159][160][161] Here miscommunication (outcome) occurred because doctors and patients had different perceptions of the role of the family.…”
Section: Social Component Of Communicationmentioning
confidence: 99%
“…De acuerdo a la evidencia internacional, la problemática de salud y uso de servicios sanitarios por parte de niños migrantes se resume en: (i) el acceso difícil y el desconocimiento del nuevo sistema de atención de la salud; (ii) las barreras del idioma; (iii) las diferencias en expectativas y necesidades percibidas por parte de este grupo; (iv) la divergencia en la capacidad de pago de los costos de atención de la salud; y (v) las diferencias culturales en las definiciones de enfermedad y los tratamientos esperados. Los pocos estudios disponibles en niños migrantes sugieren que las barreras idiomáticas 22 y las expectativas de los padres respecto del sistema de salud 6 son particularmente relevantes. Sobre este últi-mo punto, un estudio cualitativo de familias polacas en Escocia sugirió que las preocupaciones de los padres migrantes acerca de los servicios de salud son propensos a tener un impacto en sus creencias y comportamientos infantiles 23 .…”
Section: Introductionunclassified